The impact of culture perception on kinship disconnection of Chinese youth: examining the chain mediating effect of kinship support, kinship burnout, and social media interaction - Han, Ruixia (Frontiers in Psychology, 2023)
Kinship connections are an essential foundation of social relationships in China, yet in recent years there has been an increasing tendency toward kinship disconnection (Duanqin) among Chinese youth. In this study, based on online survey data of 555 Chinese individuals aged 18–35 years under a comprehensive explanatory framework of culturalism, functionalism, and behaviorism, regression and mediation analyses found that (1) cultural perception based on family-state values is the dominant factor influencing people’s tendency to disconnect. (2) Kinship support decreases people’s propensity to break off relatives, while kinship burnout increases people’s propensity to cut off relatives. Both act as functionalist factors in the chain that mediates the effect of cultural perception on the propensity to break kinship, and kinship burnout obscures the effect of kinship support and becomes a differentiating variable. (3) Both social media kin interaction size and kin group activity significantly reduce people’s propensity to disconnect. However, group activities are more significant in cultural perception’s mediating effect on disconnection propensity. It indicates that truly “active” social media connections are more important. The study attempts to propose a framework of “cultural perception + functional satisfaction and burnout + social media” to interpret Chinese youth kinship communication activity. On a practical level, more support for young people in social media interactions could slow or even reverse the trend of disconnection.